The relationship between crime and private security at US shopping centers - Lee, Gang (American journal of criminal justice, 1999)
This paper uses self-report data from the 1993 National Shopping Center Security Survey to examine the growing problem of crime at shopping centers located in the United States. Security managers from 369 shopping centers provided data on crime incidents, private security measures, and numerous shopping center demographic measures. Data are analyzed via LISREL using bivariate regression modeling. Results show that there is no direct relationship between the private security measures at the shopping center and the occurrence of property, violent, or public order crimes on the premises. Instead, private security presence is shaped by the size of the shopping center. Direct effects were also found between the incidence of crime on the premises and the size of the shopping center and the presence of various “problematic” persons (i.e., gangs and loitering groups of youth). Possible implications for shopping center security are considered.